1996
DOI: 10.1093/bja/77.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic effect of subhypnotic doses of propofol after thyroidectomy

Abstract: Postoperative nausea and vomiting (PONV) are unpleasant, often underestimated side effects of anaesthesia and surgery, not devoid of medical complications. Prevention with antiemetics is only partially effective. Propofol has been shown recently to possess antiemetic properties in several situations. In this prospective, randomized, controlled trial, we have compared the antiemetic efficacy of subhypnotic doses of propofol, with Intralipid as placebo, after thyroidectomy. We studied 64 patients of both sexes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 18 publications
1
66
3
Order By: Relevance
“…The overall incidence of PONV in propofol group was has reported failure of propofol in treating postoperative vomiting in children undergoing tonsillectomy. Contrary to our results, small dose of propofol was effective in thyroidectomy in trials of Ewalenko et al (1996) [3] and Fujii et al (2001) [4]. However former used continuous infusion of propofol in low dose.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of PONV in propofol group was has reported failure of propofol in treating postoperative vomiting in children undergoing tonsillectomy. Contrary to our results, small dose of propofol was effective in thyroidectomy in trials of Ewalenko et al (1996) [3] and Fujii et al (2001) [4]. However former used continuous infusion of propofol in low dose.…”
Section: Discussioncontrasting
confidence: 99%
“…Propofol an anesthetic agent possesses antiemetic action. Recent studies have reported excellent antiemetic effect of sub hypnotic dose of propofol following thyroid surgery (Ewalenko et al 1996, Fujii et al 2001 [3,4] but it has not been used for other ENT surgeries. We therefore conducted a study to investigate the possible antiemetic effect of small dose of propofol following ENT surgeries and compared it with ondansetron and metoclopramide, the most commonly used antiemetics in our ENT ward.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we only considered PONV up to the point of hospital discharge and it is possible that propofol simply delayed, rather than prevented, PONV. Although propofol is generally recognised to possess anti-emetic effects [24], these effects are relatively short lived [25].…”
mentioning
confidence: 99%
“…A high incidence of PONV has been reported in female patients undergoing thyroidectomy without antiemetic treatment. Although the reason for the high incidence of PONV after thyroidectomy is not clear, several factors are probably related to including middle-age, the female gender of patients, and vagal stimulation by the surgical handling of the neck [2,12]. In the current study, we reported that 81% of patients in the control group (Group 1) had PONV during the postoperative 24 h. This incidence was higher than that of previous studies of PONV in patients without prophylactic antiemetic treatment who underwent thyroidectomy with inhalation anesthesia (60-65%) [2,[11][12][13].…”
Section: Resultsmentioning
confidence: 99%